Business model development for orphan drug business in indonesia (case study: idiopathic pulmonary fibrosis drug) - Veronica Hutagalung, Donda Ria; Hamsal, Mohammad (The Indonesian Journal of Business Administration, 2019)
Abstract. The growth of pharmaceutical business has slowed due to some reasons, such as patent expiration, generic, drying pipelines, and stricter regulation of drug approval. Many market leaders will lose their patent in next 5 years. Considering those situations, pharmaceutical companies have shifted their focus from developing and selling essential medicines to new business model of orphan drugs, which is niche but expected to help company reducing the revenue loss. This new segment could offer an integrated healthcare solution through development of new area of therapeutics, diagnosis, treatment, monitoring, and patient support. Orphan drug is a product which is indicated for a rare disease. Definition of rare disease in Indonesia is a disease with case number less than 200,000 total populations. Lack of physicians’ awareness and high drug cost are the main challenges in developing orphan drug business. Implementation of Jaminan Kesehatan Nasional (JKN) program has changed Indonesian healthcare landscape drastically. The objective of this study is to propose a new business model canvas for an orphan drug business in Indonesia, by using Idiopathic Pulmonary Fibrosis drug as case study. The analysis of external factors will be done through PEST (Political, Economic, Social, Technological), Porter's 5 Forces and competitive analysis. The internal analysis will use VRIO and value chain analysis. The results of those internal and external analysis will be used to identify SWOT, develop TOWS matrix. Porter Generic Strategy and Diamond Strategy model to identify new ideas and strategies for the company. After identifying some options of business strategy, author will create and propose a new business model canvas for the company. Author will use qualitative research method by collecting data through interview and observation. The author has identified and assessed that the firm has not optimally used their internal resources and capabilities to create innovative strategies and to achieve sustainable competitive advantages. Author recommends management of the firm to reorganize their team, then to equip the new team with updated knowledge on orphan drug business. The firm should also optimally use global resources and capabilities to build orphan drug business and to develop effective digital platform. They should initiate unique partnership with multi stakeholders, especially with government and patient organization to shape public policy for orphan drug. Keywords: business strategy, business model, multinational pharmaceutical company, orphan drug, rare disease